E-059 Dural venous sinus cephaloceles in the pulsatile tinnitus clinic. (22nd July 2019) - Villanueva-Meyer, J; Eisenmenger, L; Shah, V; Meisel, K; Amans, M
Abstract : Brain herniations into the dural venous sinuses are recently described rare findings that are of uncertain etiology and clinical significance. We describe 18 instances of brain herniations into dural venous sinuses in 16 patients identified on MRI and discuss their imaging findings, possible causes, and relationship to the patient's symptoms. All patients were examined with MRI including pre- and post-contrast T1- and T2-weighted sequences. With respect to brain herniations we documented their location, signal intensity, size, presence of arachnoid granulation, and associated dural venous sinus stenosis. We then reviewed clinical records in an attempt to establish if any symptoms were related to the presence of these herniations. 262 patients who presented to our institution's Pulsatile Tinnitus Clinic over a three year period were examined. 16 patients had brain herniations into dural venous sinuses (age range 25–79). 11 patients had unilateral temporal or occipital herniations into the transverse sinus or the transverse-sigmoid sinus junction, respectively. Three patients had unilateral cerebellar herniations into the transverse sinus. One patient had bilateral temporal herniations into the transverse-sigmoid sinus junction. One patient had bilateral occipital and cerebellar herniations into the transverse sinuses. Arachnoid granulations were seen in association with 13 of the herniations. Focal dural venous sinus stenosis was associated with 15 of the 18 herniations. In 9 of 16 patients (56%) symptoms matched side of brain herniation. 9 of 16 patients (56%) had intracranial hypertension. Brain herniations into dural venous sinuses are uncommon incidental findings with an uncertain relationship to pulsatile tinnitus and intracranial hypertension. Disclosures: J. Villanueva-Meyer: None. L. Eisenmenger: None. V. Shah: None. K. Meisel: None. M. Amans: None.